Identification of the Application of Civics Learning in Online Learning during the Covid-19 Pandemic: Identifikasi Penerapan Pembelajaran PKn dalam Pembelajaran Online di Masa Pandemi Covid-19 - Mustofiyatul Mukaromah; Rifki Afandi (Universitas Muhammadiyah Sidoarjo, 2022)
This qualitative study investigates the learning planning, application of PKn (Civics) instruction, and teacher barriers in online learning for fourth-grade students during the Covid-19 pandemic. The research subjects include teachers, principals, and students from SDN Panggreh II. Data collection techniques comprise interviews, observations, and documentation, while data analysis employs the Miles and Huberman model. Findings reveal that teachers at SDN Panggreh II implemented online learning plans, encompassing syllabi, lesson plans, and learning media. However, they encountered challenges due to limited experience in online teaching and difficulties in selecting appropriate learning materials and activities. The study underscores the need for effective strategies to enhance online Civics instruction and overcome these obstacles, thereby ensuring quality education during times of crisis. Highlights: Importance of online learning: Explore the challenges and strategies involved in implementing online learning for fourth-grade students during the Covid-19 pandemic. Enhancing Civics education: Investigate the application of PKn (Civics) instruction in an online learning environment, emphasizing the need for effective learning plans and appropriate teaching methods. Teacher barriers and solutions: Identify the barriers faced by teachers, such as limited online teaching experience and difficulty selecting suitable learning materials, and propose potential solutions to overcome these challenges. Keywords: Online learning, Civics education, Fourth-grade students, Teacher barriers, Covid-19 pandemic